The role of social support in the persistence of first-year first-generation African students in a higher education institution in South Africa - Motsabi, S.; Diale, B.M.; van Zyl, A. (South African Journal of Higher Education, 2020)
Although there are several studies on first-year, first-generation students internationally, their focus have predominantly been on reasons for dropping out, transition issues and the students’ pre-entry attributes. However, few studies have focused on the first-year, first-generation African students (FYFGAS) in the African context. This article employed a qualitative inquiry to explore the role of social support in school retention among FYFGAS within the South African context. Twenty-three students in all participated in the individual interviews (n = 5) and in the focus group (n = 18) discussion. The interviews were based on questions where the research sought to understand the determinants and contributors to the students’ persistence and success in their first year of study. Themes that emerged from the data analysis indicated the important role of the family, the community at home and at university and of peers in supporting and encouraging the FYFGAS in pursuing their studies throughout their first year. Findings of this study indicated the importance of social support towards the persistence and success for FYFGAS in their first year of study at university.